Morality and homicide: a study about the transgressors action - Borges, Luciana Souza; Alencar, Heloisa Moulin de (Paidéia (Ribeirão Preto), 2009)
We investigated the judgments of representation of reality (JRR) and judgment of moral value (JMV) about transgressing actions, concerning the past and present time, of 20 homicidal men aged between 30 and 49 years. Individual interviews using the clinical piagetian method were carried out and the following were verified: the most cited JRR in the past was the one that they would commit the homicide again, due the suffered humiliation or the experienced negative feeling; in the present they reported they would not kill again due to the crime negative consequences, to their own or the victim's characteristics and lifes value; the JMV most mentioned in the past was the one that the action would be wrong due the negative consequences; in the present all of them considered wrong the committed homicides due to the negative consequences, value attributed to life and religious reasons. We expect that this discussion permit a deeper understanding of the homicidal individual so that universal principles such as respect for life can be taught and taken into consideration.